D-oscillons in the standard model extension - Correa, R. A.C.; Da Rocha, Roldão; De Souza Dutra, A. [UNESP] (American Physical Society (APS), 2015)
In this work we investigate the consequences of the Lorentz symmetry violation on extremely long-lived, time-dependent, and spatially localized field configurations, named oscillons. This is accomplished for two interacting scalar field theories in (D+1) dimensions in the context of the so-called standard model extension. We show that D-dimensional scalar field lumps can present a typical size Rmin RKK, where RKK is the extent of extra dimensions in Kaluza-Klein theories. The size Rmin is shown to strongly depend upon the terms that control the LV of the theory. This implies either contraction or dilation of the average radius Rmin, and a new rule for its composition, likewise. Moreover, we show that the spatial dimensions for existence of oscillating lumps have an upper limit, opening new possibilities to probe the existence of D-dimensional oscillons at TeV energy scale. In addition, in a cosmological scenario with Lorentz symmetry breaking, we show that in the early Universe with an extremely high energy density and a strong LV, the typical size Rmin was highly dilated. As the Universe had expanded and cooled down, it then passed through a phase transition toward a Lorentz symmetry, wherein Rmin tends to be compact.